Evaluation of the Implementation of Minimum Pharmaceutical Service Standards in Indonesian Hospitals: A Systematic Review - Yarnida Kurniati; Elin Yulinah Sukandar (Jurnal FARMASIMED (JFM), 2026)
Pharmaceutical services play a crucial role in ensuring patient safety and healthcare. Evaluation of the implementation of Minimum Service Standards (SPM) for pharmacy is an instrument for measuring the performance of healthcare institutions in providing quality and efficient services. This systematic review aims to evaluate the implementation of SPM for pharmacy in Indonesian hospitals based on four main indicators, influencing factors, and suggested intervention strategies. The systematic review method adopted the PRISMA guidelines through the Google Scholar electronic database. The evaluation results show variations for each indicator: waiting time 4-38.1 minutes, waiting time for compounded medication 8-≥60 minutes, no medication errors 90-100%, formulary compliance 89.3-100%, and patient satisfaction 53.6-94%. In conclusion, SPM for pharmacy has not been fully implemented in Indonesian hospitals. The main factors causing non-compliance with established standards include limited number of pharmacists, incompletely integrated information systems, and suboptimal drug inventory management. Intervention strategies can be implemented through recruitment of qualified pharmacists; ongoing training programs; implementation of an integrated management information system in the form of electronic prescriptions; and digital queuing system, the formation of a quality team to evaluate the Minimum Service Standards for pharmacies in hospitals, and multi-professional collaboration between pharmacists, doctors and management to ensure optimal service delivery.